2018
DOI: 10.1111/1753-6405.12748
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the use of economic evidence to inform investment in disease prevention – a qualitative study

Abstract: Objective: In the context of growing financial pressures on health budgets, cost-effective prevention strategies are needed to address the burden from non-communicable disease in Australia. We explored how decision makers use economic evidence to inform such investment and how such evidence generated can more effectively meet the needs of end users.Methods: Thematic analysis of in-depth interviews with 15 high level stakeholders (Treasury, state health departments and the insurance industry), supplemented by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…This was highlighted in the questionnaire results where all Health participants agreed that there was inadequate capacity within the department to complete economic evaluations. Building capacity to understand health economics within the NSW Ministry of Health has been previously recommended [ 34 ]. However, in addition to building an understanding of the basics of health economics, this study found that there was a need for more advanced skills that could be fulfilled by a health economics group embedded within the NSW Ministry of Health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was highlighted in the questionnaire results where all Health participants agreed that there was inadequate capacity within the department to complete economic evaluations. Building capacity to understand health economics within the NSW Ministry of Health has been previously recommended [ 34 ]. However, in addition to building an understanding of the basics of health economics, this study found that there was a need for more advanced skills that could be fulfilled by a health economics group embedded within the NSW Ministry of Health.…”
Section: Discussionmentioning
confidence: 99%
“…A previous descriptive study by Liu et al [ 34 ] explored the factors that drive decisions on evidence-based policy-making related to preventive health by Australian governments and private health insurers. A key finding was that perspectives varied between representatives from health and treasury departments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, this study sheds some light on the challenges that lie ahead when trying to reconcile the different logics of health economics and health promotion. In a recent review of the use of economic evidence to inform disease prevention policy, Liu et al found that capacity in the health sector to understand economic evidence on interventions is limited and that capacity-building is needed to promote the use of this evidence ( Liu et al , 2017 ). The feedback from our partners mirrors these findings, indicating that health promotion research experts may find the logic and methods employed by health economics hard to understand.…”
Section: Discussionmentioning
confidence: 99%
“…New partnerships and collaborations might also mean applying research methods from other disciplines, such as law, economics, environmental and political science. Some of the Prevention Centre's more recent work includes using public health law to analyse prevention decisions, 34 applying economic tools to measure and assess the value of prevention, 35,36 and researching community attitudes about government intervention for prevention to support and inform decision‐making by the Centre's policy partners 37 …”
Section: New Ways Of Thinking For Chronic Disease Preventionmentioning
confidence: 99%